The Clinician and Dataset Shift in Artificial Intelligence - Finlayson, Samuel G; Subbaswamy, Adarsh; Singh, Karandeep; Bowers, John; Kupke, Annabel; Zittrain, Jonathan; Kohane, Isaac S; Saria, Suchi (The New England journal of medicine, 2021)
This letter outlines how to identify, and potentially mitigate, common sources of “dataset shift” in machine-learning systems. This occurs when the model “training data” differ from the data used by the model to provide diagnostic, prognostic, or treatment advice.